2020
DOI: 10.3390/beverages6040068
|View full text |Cite
|
Sign up to set email alerts
|

Natural Nrf2 Activators from Juices, Wines, Coffee, and Cocoa

Abstract: Juices, wine, coffee, and cocoa are rich sources of natural polyphenolic compounds that have potent antioxidant activities proven by in vitro and in vivo studies. These polyphenolic compounds quench reactive oxygen and nitrogen species (RONS) or reactive free radicals and act as natural antioxidants which are also able to protect against reactive oxygen species (ROS)-mediated oxidative damage, which elevates cellular antioxidant capacity to induce antioxidant defense mechanisms by modulating transcription fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 132 publications
0
14
0
3
Order By: Relevance
“…This pathway is activated when Keap1-thiol residues are modified by free radicals or electrophiles (such us phytochemical electrophiles), which allows Nrf2 release and translocation to the nucleus, where it binds to antioxidant element response (ARE) or electrophile-response element (EpRE) at the promoters of Nrf2-induced genes, including γ-glutamyl cysteine synthetase (γ-GCS), heme oxygenase 1 (HO-1), glutathione reductase (GR), glutathione peroxidase (GPx), thioredoxin-1, thioredoxin reductase, catalase (CAT), NAD(P)H:quinone oxidoreductase-1 (NQO1), superoxide dismutase (SOD) and peroxiredoxins [ 83 ]. The protein products of these genes are involved in the elimination of reactive species and drug detoxification [ 84 ]; additionally, it is important to note that recent studies have revealed new targets genes of Nrf2 and for instance has pointing out new functions of the Keap1-Nrf2 pathway, such us metabolic reprogramming, unfolded protein response and proteostasis, autophagy, mitochondrial physiology and biogenesis and, inflammation and immunity [ 85 ] .…”
Section: Resultsmentioning
confidence: 99%
“…This pathway is activated when Keap1-thiol residues are modified by free radicals or electrophiles (such us phytochemical electrophiles), which allows Nrf2 release and translocation to the nucleus, where it binds to antioxidant element response (ARE) or electrophile-response element (EpRE) at the promoters of Nrf2-induced genes, including γ-glutamyl cysteine synthetase (γ-GCS), heme oxygenase 1 (HO-1), glutathione reductase (GR), glutathione peroxidase (GPx), thioredoxin-1, thioredoxin reductase, catalase (CAT), NAD(P)H:quinone oxidoreductase-1 (NQO1), superoxide dismutase (SOD) and peroxiredoxins [ 83 ]. The protein products of these genes are involved in the elimination of reactive species and drug detoxification [ 84 ]; additionally, it is important to note that recent studies have revealed new targets genes of Nrf2 and for instance has pointing out new functions of the Keap1-Nrf2 pathway, such us metabolic reprogramming, unfolded protein response and proteostasis, autophagy, mitochondrial physiology and biogenesis and, inflammation and immunity [ 85 ] .…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have reported that hypoxia-induced oxidative stress inhibits the first-line antioxidant defense, made up of CAT, SOD, and GPx in the liver of freshwater fish [9,14]. In this regard, PCs can increase the antioxidant defenses during oxidative stress via the nuclear factor derived from erythroid 2 (Nrf2) activation, inducing the transcription of the antioxidant enzymes CAT, SOD, and GPx [32,33], which maintain homeostasis of the redox state through the suppression or prevention of the ROS formation in cells to prevent oxidative damage [7,34]. First, SOD dismutate the O 2…”
Section: Discussionmentioning
confidence: 99%
“…A myriad of ingredients that are used daily and have the ability to promote the nuclear translocation of Nrf2 are reported in Table 1 . Among these, spices were demonstrated to have potential as natural Nrf2 pathway activators that can be used in disorders caused by OS [ 130 , 131 ].…”
Section: Therapeutic Options In Htnmentioning
confidence: 99%